Rapid identification of genome-edited mesenchymal stem cell colonies via Cas9 - Wei Jiang; Wei Lian; Jieting Chen; Wenlei Li; Jieyong Huang; Baoyu Lai; Lingyun Li; Zhong Huang; Jianyong Xu (BioTechniques)
Mesenchymal stem cells (MSCs) have been intensively investigated and widely applied in regenerative medicine and immune modulation. However, their efficacy declines during the aging or disease process. Thus, genome-edited MSCs with over-expression or inhibition of specific genes hold a great deal of promise in terms of their therapeutic application. Here we optimized the direct PCR approach for rapid identification of genome-edited MSCs with only ten cells required, which reduces the time and labor to expand the MSC colonies. Combined with our previously optimized guide RNA structure and plasmid construction strategy for Cas9, we successfully identified MSC colonies over-expressing IL-10 in the AAVS1 locus.